Food for Freedom, Inc., records - Food for Freedom, Inc.; Weston, Harold, 1894-1972.
Correspondence, memoranda, minutes, speeches, reports, articles, notes, news releases, reprints, clippings, cartoons, and other records of Food for Freedom, Inc., including the manuscript "Battle of Bread" written by Harold Weston in 1948. Organizations represented include the Food and Agriculture Organization of the United Nations, International Emergency Food Council, Reconstruction Service Committee, UNICEF, United Nations Relief and Rehabilitation Administration, and the U.S. President's Famine Emergency Committee. Correspondents include Louis Adamic, Phillip Jessup, Eleanor Roosevelt, and James Thomson Shotwell.
World War II civilian relief organization directed by Harold Weston, modernist painter who devoted his work during the World War II period to combating hunger among refugees in Europe and Asia.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adamic, Louis, -- 1899-1951 -- Correspondence; Jessup, Philip C. -- 1897-1986 -- Correspondence; Roosevelt, Eleanor, -- 1884-1962 -- Correspondence; Shotwell, James T., -- 1874-1965 -- Correspondence; Weston, Harold, -- 1894-1972.; United States. -- President's Famine Emergency Committee; Food and Agriculture Organization of the United Nations; International Emergency Food Council; Reconstruction Service Committee; UNICEF; United Nations Relief and Rehabilitation Administration; Reconstruction (1939-1951); World War, 1939-1945 -- Civilian relief; World War, 1939-1945 -- Food supply